Impacts of industry 4.0 on operations management: challenges for operations strategy - Gaspar, Marcelo (2020)
The digital transformation of business positively contributes to the creation of new opportunities and challenges for Operations Management. New technologies have made it possible for managers to access, store and process large amounts of data, collected from different complementary sources, both internal and externally to processes. Nonetheless, even though such data availability may be of great contribution for management at the operational level, its potential for value creation at the operations strategy level remains unclear. The purpose of this paper is to explore the impacts of recent trends and features related to the digita transformation in the operations management field, namely to further understand how such digital transformation is going to impact the operations strategy definition.